Maudsley International: improving mental health and well-being around the world. (19th March 2018) - Bouras, Nick; Davey, Silvia; Power, Tracey; Rolfe, Jonathan; Craig, Tom; Thornicroft, Graham
Abstract : Maudsley International was set up to help improve people's mental health and well-being around the world. A variety of programmes have been developed by Maudsley International over the past 10 years, for planning and implementing services; building capacity; and training and evaluation to support organisations and individuals, professionals and managers to train and develop health and social care provisions. Maudsley International's model is based on collaboration, sharing expertise and cultural understanding with international partners.